2015
DOI: 10.1097/ajp.0000000000000142
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Analgesia and Efficacy of Ibuprofen Sodium in Postsurgical Dental Pain

Abstract: Objectives:A novel, immediate-release tablet formulation of ibuprofen (IBU) sodium dihydrate, Advil Film Coated Tablets (IBUNa), has been developed that is absorbed faster than standard IBU tablets. The objective of the current study was to compare the efficacy and onset of analgesia of this new formulation with standard IBU tablets after a single dose.Materials and Methods:Patients (N=316) with at least moderate baseline postsurgical dental pain were randomized to 400 mg IBUNa, Advil (IBUAdv), Motrin (IBUMot)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…6 It had a measurable effect on faster action and earlier pain relief. [7][8][9][10] The ibuprofen anion can also be paired with organic cations, such as for the amino acids lysine, arginine and polylysine, in which the positive charge is located on the nitrogen atom of the amino group. [11][12][13][14] Ibuprofen arginine or lysine salts, similar to its sodium salt, showed better solubility and a higher mean maximum plasma or serum ibuprofen concentration in a shorter time.…”
Section: Introductionmentioning
confidence: 99%
“…6 It had a measurable effect on faster action and earlier pain relief. [7][8][9][10] The ibuprofen anion can also be paired with organic cations, such as for the amino acids lysine, arginine and polylysine, in which the positive charge is located on the nitrogen atom of the amino group. [11][12][13][14] Ibuprofen arginine or lysine salts, similar to its sodium salt, showed better solubility and a higher mean maximum plasma or serum ibuprofen concentration in a shorter time.…”
Section: Introductionmentioning
confidence: 99%
“…The two dental pain studies (NCT01098747 [13] and NCT01216163 [14]) enrolled subjects aged between 16 and 40 years with at least moderate postoperative pain at baseline following surgical extraction of ‡ 2 third molars, ‡ 1 of which was a partial or complete mandibular impaction. Participants in the two headache studies (NCT01077973 [15] and NCT01362491 [16]) were aged between 18 and 65 years and had a history of episodic tension-type headache of moderately severe to severe intensity that was usually relieved by OTC analgesics.…”
Section: Methodsmentioning
confidence: 99%
“…In pharmacokinetic studies, this formulation of IBU Na was absorbed faster -as demonstrated by higher maximal concentration (C max ) and shorter time to reach C max (T max ) -than standard IBU tablets and absorption was as fast as solubilized IBU and IBU lysine [12]. In a clinical study of patients with postoperative dental pain, IBU Na provided more rapid onset of analgesia than standard IBU tablets [13]. Although the safety profile of IBU Na is expected to be the same as standard IBU, it is conceivable that faster absorption of IBU Na , resulting in higher and more rapidly attained peak IBU plasma levels, could adversely affect the safety and tolerability profile compared with standard IBU.…”
Section: Introductionmentioning
confidence: 96%
“…Additional patient assessments included time to first perceptible relief (TFPR) and time to meaningful pain relief (TMPR) using the double-stopwatch method [16], in which the first stopwatch was pressed by the patient when pain relief was first perceived, and the second when that relief became meaningful. Duration of pain relief was measured by the time to treatment failure (i.e., the time of first dose of rescue medication or dropout because of lack of efficacy).…”
Section: Study Assessments and Endpointsmentioning
confidence: 99%